THE INFLUENCE OF CONSUMER CONFIDENCE AND EASE OF TRANSACTIONS ON ONLINE SHOPPING INTERESTS IN STUDENTS OF THE INDONESIAN COLLEGE OF MANAGEMENT SCIENCE SAMARINDA - Sattar Sattar; Mihani Mihani; Anggraeni Salsadila Yunus (International Journal of Economy, Education and Entrepreneurship, 2021)
This study aims to examine and analyze the effect of consumer trust and ease of transactions on online shopping interest in students of the Indonesian College of Management Sciences (STIMI) Samarinda. This research was conducted from March to May 2021. The study population was students of the Indonesian College of Management Sciences (STIMI) Samarinda class 2017, 2018, and 2019, with 126 people and a sample of 96 respondents. Sampling was done by using a questionnaire. Based on the results of multiple linear regression, it is stated that if each independent variable (X1 and X2) is considered zero, then the Y prediction is 3.821. The predictor coefficient of consumer confidence (X1) of 0.076 indicates that consumer confidence can positively predict online shopping interest. The predictor coefficient of transaction convenience (X2) of 0.0280 indicates that the ease of transactions can positively predict online shopping interest. Based on the calculation of the t-test analysis, it says that consumer confidence (X1) has no significant effect because tcount > ttable (1.863 > 1.661), which is significantly greater than 0.05, which is 0.070. The ease of transaction variable (X2) has a significant effect because tcount > ttable (3.619 > 1.661). Based on the F test, it can be concluded that consumer trust (X1) and ease of transaction (X2) have a significant effect on online shopping interest (Y). Where fcount > ftable (16.941 > 3.094).Based on the coefficient of determination R2 (R square) of 0.251 (25.1%). This shows that the percentage of the influence of the independent variables (consumer trust and ease of transactions) on the dependent variable (online shopping interest) is 25.1%, while the remaining 74.9% is influenced by other variables not included in this research model